High-order harmonic spectroscopy in an ionized high-density target - Kurz, Heiko G.; Kretschmar, Martin; Binhammer, Thomas; Nagy, Tamas; Ristau, Detlev; Lein, Manfred; Morgner, Uwe; Kovačev, Milutin (Frontiers in Physics, 2022)
We use high-order harmonic spectroscopy to develop a figure of merit for ionization in a macroscopic target with tunable density, spanning over six orders of magnitude. In an in-situ pump-probe experiment, the target is prepared at different densities with varying degrees of laser-induced ionization. High-order harmonic radiation is generated in the pre-ionized target, and a steepening in the decrease of the harmonic yield is observed for increasing pre-ionization, allowing not only to identify contributing quantum paths during high-order harmonic generation but also to determine the amount of ionization within the target. The measurements allow to probe ionization dynamics in plasma physics with high spatio-temporal resolution and are especially of interest for the optimization of the harmonic generation process in high-density targets with number densities of up to \SI{e22}{cm^{-3}}.